2011
DOI: 10.1590/s0366-69132011000100008
|View full text |Cite
|
Sign up to set email alerts
|

The mineralogical and fabric analysis of ancient pottery artifacts

Abstract: The present investigation is carried out to estimate the firing temperature and conditions of firing of ancient pottery shreds excavated recently from Sembiankandiyur, Tamil Nadu, India. FTIR and XRD studies have been attempted on these shreds to characterize the mineral composition of the pottery artifacts in respect of their different physical attributes. The firing temperature and conditions were inferred from the mineral phases of the samples exhibited by the infrared spectra and X-ray diffractograms recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 16 publications
1
36
0
3
Order By: Relevance
“…The absence of hematite and magnetite in the XRD patterns of brown and black coloured sherds can be explained by a quantity lower than the detection limit of XRD [10]. Hematite is one of the most intense colouring materials and only 1-1.5% of hematite is sufficient to give the pottery a reddish colour [1]. Thermal analysis: the thermal analysis of the 17 selected ceramics yielded almost similar results, which showed two thermal behaviours or two thermal groups of ceramics, according to the presence or absence of an exothermic peak between 250-450 °C.…”
Section: Ceramicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of hematite and magnetite in the XRD patterns of brown and black coloured sherds can be explained by a quantity lower than the detection limit of XRD [10]. Hematite is one of the most intense colouring materials and only 1-1.5% of hematite is sufficient to give the pottery a reddish colour [1]. Thermal analysis: the thermal analysis of the 17 selected ceramics yielded almost similar results, which showed two thermal behaviours or two thermal groups of ceramics, according to the presence or absence of an exothermic peak between 250-450 °C.…”
Section: Ceramicsmentioning
confidence: 99%
“…The presence of the exothermic peak between 250-500 °C (DTA) can be explained by the combustion of organic material contained in these samples [12,13]. According to Palanivel et al [1] the exothermic effect observed within the range 200-650 °C is attributed to the combustion of organic materials, not completely burnt during firing in reducing condition and transformed into carbonaceous particles, which are thought to have been deliberately added into ceramic paste to increase its plasticity, or were contained in the clay utilized in the manufacture. It has been suggested that the organic materials might have been added as a binder in the preparation of the pottery or in manufacturing external surface coating, for example albuminous [14].…”
Section: Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…대부분의 시료는 내외부 의 색 차이를 보이는데 외면은 어두운 회색계열, 속심은 적색계열을 나타내고 있다( Table 1). 이는 태토 내에 포함되어있던 미량의 철이 산화되면서 속심은 갈색에서 적갈색의 색을 띠는 한편, 토기의 외면은 고온에서 환원환경의 영향을 받았다고 추 정할 수 있으며 (Velraj et al, 2008;Palanivel and Kumar, 2009;Rutherford et al, 2012 …”
Section: 토 의unclassified
“…Furthermore, characterization of historical ceramics provides important information for conservation and restoration methods [6,7]. To study the production and firing technologies, spectroscopic techniques are applied to determine the chemical and mineralogical compositions, and therefore the firing temperature of the ceramic sherds through the detection of phase transformations and firing minerals that occur during the firing process [8][9][10]. Usually, one technique is not enough to characterize and define chemical composition and firing temperature in ceramic sherds, and in the Cultural Heritage field the use of non-destructive and non-invasive techniques is required.…”
Section: Introductionmentioning
confidence: 99%